2007
DOI: 10.1159/000104457
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Regulation of Glucose Transport, Anaerobic Metabolism and Angiogenesis in Cancer: Novel Pathways and Targets for Anticancer Therapeutics

Abstract: Cancer cells require a steady source of metabolic energy in order to continue their uncontrolled growth and proliferation. Accelerated glycolysis is one of the biochemical characteristics of cancer cells. Recent work indicates that glucose transport and metabolism are essential for the posttreatment survival of tumor cells, leading to poor prognosis. Glycolytic breakdown of glucose is preceded by the transport of glucose across the cell membrane, a rate-limiting process mediated by facilitative glucose transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
209
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(221 citation statements)
references
References 312 publications
10
209
0
2
Order By: Relevance
“…Previous study showed Glut1 expression was regulated by hypoxia, and HIF-1α might be involved in this regulation (Airley et al, 2007). Our data have demonstrated that the expression of Glut1 is regulated by miR-186, and downregulation of miR-186 increases glucose uptake and lactate production through upregulation of Glut1 during CAF formation.…”
Section: Discussionsupporting
confidence: 58%
“…Previous study showed Glut1 expression was regulated by hypoxia, and HIF-1α might be involved in this regulation (Airley et al, 2007). Our data have demonstrated that the expression of Glut1 is regulated by miR-186, and downregulation of miR-186 increases glucose uptake and lactate production through upregulation of Glut1 during CAF formation.…”
Section: Discussionsupporting
confidence: 58%
“…Glucose transporter 3 (GLUT3) is induced in many cancer cells lines, as well as during hypoxia, and is responsible for increased glucose uptake (14). GLUT3 protein levels are greatly increased in endothelial cells latently infected with KSHV as determined by Western blot analysis with anti-GLUT3 antibodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cancerous cells grow and multiply faster than normal cells, resulting in an acutely increased demand for energy (6). The up-regulation of hGLUT1 upon increased demand for glucose highlights it as an important prognostic indicator in several cancer types (7)(8)(9)(10), as well as a potential new target for therapeutic inhibitors.…”
mentioning
confidence: 99%